Cancer mortality trends after implementation of the national programme for dispensarization of certain groups of the adult population: a population-based study from arkhangelsk, north-western russia - L. E. Valkova; M. L. Levit; V. M. Merabishvili; A. Yu. Pankrateva; M. V. Krupina; D. M. Dubovichenko; A. V. Agaeva; A. Yu. Ryzhov; E. F. Potekhina; M. Yu. Valkov (Исследования и практика в медицине)
Purpose of the study.To conduct a comparative analysis of the mortality from malignant neoplasms (MNs) detected during the implementation of the oncological component of National Prevention Programme named Dispensarization of certain groups of the adult population (DCGAP) according to the data of the Arkhangelsk Regional Cancer Registry (ARCR) for the period from 2006 to 2019.Materials and methods. Anonymous data about patients with malignant neoplasms of the colon, rectum, lung, breast, cervix, uterus, ovaries, prostate gland, kidney undergoing examination (screening) at the first stage of the DCGAP from 2006 to 2019 were extracted from the ARCR database. We compared the averaged crude and age-standardized (WHO world standard 2001) mortality rates in the periods before (2006–2012) and after the implementation of DCGAP (2013–2019) in the entire population, as well as in men and women and in age groups 15–59 years old for males and 15–55 years old for the female population ("mortality at working age") and 30–69 years old ("premature mortality"). A segmented analysis of the mortality rates was carried out. The interventional value of the DCGAP was positive in the case of a decrease in the linear trend in mortality between 2013 and 2017.Results. A total of 33,824 deaths were included in the analysis. 25106 (74.2%) patients died from iMN, the proportion of deaths from other causes varied from 14% for lung cancer to 83% for cervical and prostate cancer. The crude mortality rate after the introduction of DCGAP increased for all iMNs, except for cervical cancer, while age standardized rate only for cancers of the uterus and prostate. In lung cancer, there was a decrease in age-standardized mortality rates for men from 64.7 to 60.3 per 100,000 population and an increase from 5.1 to 6.5 per 100,000 for women. Mortality rates “at working age” were low for all iMNs except for cervical and breast cancers and did not differ between periods; “premature mortality” decreased only in lung cancer in men from 40.1 to 36.2 per 100,000 population, with other iMNs differences between periods were not revealed. Segmented analysis revealed no significant changes in mortality trends.Conclusion. There was no decrease in mortality among all nine iMNs in the period after the introduction of DCGAP, which is probably due to increased incidence and insufficient follow-up for later period. A comparative analysis of survival is required.